Six-Membered Cyclic Amidines as Efficient Catalysts for the Synthesis of Cyclic Dithiocarbonates from Carbon Disulfide and Epoxides under Mild Conditions - Aoyagi, Naoto; Endo, Takeshi (Synlett, 2020)
Six-membered cyclic amidines effectively catalyzed the reaction of carbon disulfide with epoxides under mild conditions, such as atmospheric pressure and ambient temperature, to give the corresponding cyclic dithiocarbonates (1,3-oxathiolane-2-thiones) in high yields.
Keywords: amidines; organocatalysis; carbon disulfide; epoxides; cyclic dithiocarbonates; oxathiolanethiones